Effects of Age and Gender on Acute Postoperative Pain after Cataract Surgery under Topical Anesthesia and Sedation - Darioush Moradi-Farsani; Khosrou Naghibi; Shiva Taheri; Babak Ali-Kiaii; Mojtaba Rahimi-Varposhti (مجله دانشکده پزشکی اصفهان, 2017)
Background: Pain is often managed inadequately and there is no general agreement on the effects of age and gender in pain perception. We performed this study to evaluate the effects of age and gender on acute postoperative pain after cataract surgery.